Ethnographic Study of Parenting Patterna for Prental Period to 3 Years on Sundanese Communities in Kampung Pasir Kaler, Cigugur, Kuningan - Andrisyah Andrisyah; Asih Nur Ismiatun; Anita Rakhman; Rita Nurunnisa (SEAMEO CECCEP, 2022)
Indonesia is a diverse country with a rich cultural heritage that influences its people's lifestyles, including parenting practices. However, it appears that modern parenting influences the bulk of parenting styles in Indonesia. The purpose of this study is to investigate the practice of prenatal care up to the age of 3 in the Sundanese community of Kampung Pasir Kaler in Kuningan, West Java. An ethnographic study was employed to reveal the facts pertaining to the aforementioned emphasis. Four pregnant women and three children aged 0 to 3 years old were involved in this study. They were selected by using the purposive sampling technique. Observation, interviews, and documentation were exerted to solicit the required data. The data analysis technique used data display, data reduction and conclusions from Milles and Huberman’s interactive model of data analysis. The findings revealed that cultural based parenting was still performed in the Sundanese community of Kampung Pasir Kaler and that there was considerable cooperation among father, mother, and the community. Penance honing, silih asah, silih asih, and silih asuh are essential values in culture-based parenting that provide distinctiveness and a clearer perspective of parenting practices that exist among Sundanese people in Indonesia. This study adds ethnoparenting data for future studies, especially parenting culture in Indonesia.